Special strength trainings in elite wrestling sports - Dvorkin, L. S.; Akhmetov, S. M.; Dvorkina, N. I. (Theory and Practice of Physical Culture, 2019)
The article analyzes the key issues of modern special strength trainings in elite wrestling sports - that are still contradictory for the research community. Clear responses still need to be found, for example, to at least the following questions: can the high-intensity strength trainings meaningfully improve the action speed in wrestling or they rather cause an adverse effect; what are the benefits of the high-intensity short strength trainings versus the low-intensity long ones for wrestling sports; shall we find the best proportions of the special strength trainings and traditional strength trainings in elite wrestling sport; what shall be the optimal proportions of the dynamic to isometric maximal-strength trainings for elite wrestling sports etc. Therefore, at this juncture the modern wrestling sport theory and practice still need to find the core solutions to offer new developments for the elite training systems and pave the ways for the theoretical knowledge being efficiently applied to improve the elite wrestlers` training models and tools.